IDENTIFIKASI KUALITATIF FENOLIK DAN PENAPISAN AKTIVITAS PEREDAMAN RADIKAL DPPH MENGGUNAKAN KLT PADA EKSTRAK BATANG Pluchea indica L. - Ni Putu Ermi Hikmawanti; Agustin Yumita; Jihan Esa Siregar (Fakultas Farmasi UMI, 2022)
Pluchea indica L. (beluntas) from the Asteraceae is a plant known to be rich in phenolics. Studies on the phenolic content of P. indica stems have not been explored much. The purpose of this study is to qualitatively identify the presence of phenolic compounds and to screen for the radical scavenging ability of DPPH in P. indica stem extracts using the TLC method. Extraction was carried out with the ultrasonic directly and sequentially using 50% ethanol as solvent. Separation was carried out on a silica gel plate GF254 with ethyl acetate: water: formic acid: toluene (20:2:2:1) as the mobile phase. Gallic acid and chlorogenic acid were used as comparisons. Identification of the presence of phenolic using FeCl3 5% as a spray reagent, while screening for radical scavenging activity using DPPH 0.1 mM as a spray reagent. The results showed that the 50% ethanol extracts of P. indica stems, both obtained from direct and stratified extraction, indicated the presence of phenolic compounds as antioxidants. The phenolic compounds detected were identical to gallic acid and chlorogenic acid, respectively, at hRf values of 89.4 and 55.3. The development of phenolic utilization from P. indica stems as a source of antioxidants still needs to be studied.